Notes on Houses and Lifestyles of Milanese Luxury Merchants. From the Reports of an Adultery Trial (1446-1447) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The judicial depositions gathered after an adultery give us the opportunity of «enter the house» of a milanese merchant of luxury goods. The large dimension of the spaces, the cohabitation of residential rooms and laboratories, the presence of workers during the night, are common here and in other milanese houses. Focusing the attention on this category of businessmen, we consider their relations with princes and courts, their principal clients, their choices of investment and consumption.
Keywords: Duchy of Milan (15th century); Luxury market; Merchants houses in Milan